The Influence of Welding Parameters on the Performance of Ultrasonic-Welded Copper-to-Copper Joints - Koen Faes; Rafael Nunes; Sylvia De Meester; Wim De Waele; Hetal Parmar; Vitantonio Esperto; Felice Rubino (Journal of Manufacturing and Materials Processing)
Copper joints are indispensable in electronics and the electrical power industry due to their predominant usage in battery pack manufacturing for electric vehicle). Traditional joining methods are often limited by oxidation-related challenges. Recent efforts have focused on addressing these limitations by employing solid-state techniques like ultrasonic welding (USW) for joining similar metals. USW presents attractive advantages such as a lower processing temperature and shorter weld time. This study investigates the ultrasonic welding of Cu-Cu joints with a thickness of 0.5 mm, focusing on both mechanical and metallurgical properties. The influence of key process parameters, such as the welding time, pressure and vibration amplitude, was examined in relation to the welding energy and lap shear strength. Additionally, the relationship between the input energy and lap shear strength was explored. A Pareto chart analysis revealed the standardized effects of these parameters on the welding energy and average lap shear strength. The welding time had a significant influence on the welding energy, while the vibration amplitude had the greatest impact on the joint strength. Longer weld times of 2.50 to 4 s yielded a higher lap shear strength, averaging up to 2.30 kN. Notably, a higher lap shear strength was achieved at lower welding energy levels.